Understanding beyond language: perceiving meaning in reality - Scott, C. D. (Koers, 2011)
This article is an attempt to develop a counter-argument to the contention that meaning is bound by language. Locating itself within the realist ontology of language developed by Saint Anselm of Canterbury, it will be argued that language comprises representations of entities perceived both extra to the perceiver and through introspection. Thus, a language game cannot be a closed system in the sense that by its very existence representations of extralinguistic being are contained therein. If truth is defined as that which is the case, the task of the perceiver becomes apprehension of being beheld without the cloud imposed by symbols: representations are not what they represent, instead they serve as windows onto a view of what is. Following exploration of psychological studies on contemplation, it is argued that it is in desymbolised moments of attentive awareness of being that meaning, unfiltered by the representativeness of language (and indeed, other symbolic systems), can arise. It will be proposed that in contemplative traditions, being is not reduced in perception, and the moment of meaning comes to the fore in the engagement and encounter with being.